Identification of Catalposide Metabolites in Human Liver and Intestinal Preparations and Characterization of the Relevant Sulfotransferase, UDP-glucuronosyltransferase, and Carboxylesterase Enzymes - Deok-Kyu Hwang; Ju-Hyun Kim; Yongho Shin; Won-Gu Choi; Sunjoo Kim; Yong-Yeon Cho; Joo Young Lee; Han Chang Kang; Hye Suk Lee (Pharmaceutics, 2019)
Catalposide, an active component of Veronica species such as Catalpa ovata and Pseudolysimachion lingifolium, exhibits anti-inflammatory, antinociceptic, anti-oxidant, hepatoprotective, and cytostatic activities. We characterized the in vitro metabolic pathways of catalposide to predict its pharmacokinetics. Catalposide was metabolized to catalposide sulfate (M1), 4-hydroxybenzoic acid (M2), 4-hydroxybenzoic acid glucuronide (M3), and catalposide glucuronide (M4) by human hepatocytes, liver S9 fractions, and intestinal microsomes. M1 formation from catalposide was catalyzed by sulfotransferases (SULTs) 1C4, SULT1A1*1, SULT1A1*2, and SULT1E1. Catalposide glucuronidation to M4 was catalyzed by gastrointestine-specific UDP-glucuronosyltransferases (UGTs) 1A8 and UGT1A10; M4 was not detected after incubation of catalposide with human liver preparations. Hydrolysis of catalposide to M2 was catalyzed by carboxylesterases (CESs) 1 and 2, and M2 was further metabolized to M3 by UGT1A6 and UGT1A9 enzymes. Catalposide was also metabolized in extrahepatic tissues; genetic polymorphisms of the carboxylesterase (CES), UDP-glucuronosyltransferase (UGT), and sulfotransferase (SULT) enzymes responsible for catalposide metabolism may cause inter-individual variability in terms of catalposide pharmacokinetics.